Exploring Halal Awareness in Cosmetic Consumption among Generation Z: Evidence from University Students in Surabaya - Audrey Fauziyah; Aini Furoida; Hapsari Ayu Kusumawardhani (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
This study aims to examine the level of halal awareness and fanaticism among university students in Surabaya and their influence on purchasing decisions for cosmetic products. A mixed methods approach was employed, combining quantitative and qualitative techniques. The quantitative data were collected through questionnaires and analyzed using descriptive statistical methods, while qualitative insights were obtained through in-depth interviews. The sample consisted of 400 undergraduate students from five public universities in Surabaya, namely Universitas Airlangga, Universitas Negeri Surabaya, Universitas Pembangunan Nasional Veteran Jawa Timur, Universitas Islam Negeri Sunan Ampel, and Institut Teknologi Sepuluh Nopember, selected using quota sampling. In addition, in depth interviews were conducted with five key informants representing four stakeholder groups: academia, business, government, and community, selected through purposive sampling. The findings indicate that the majority of respondents demonstrate a high level of halal awareness and exhibit strong fanaticism toward halal cosmetic products, which significantly influences their purchasing decisions. These results highlight the importance of halal considerations in shaping consumer behavior among Generation Z in urban Indonesia.